2013
DOI: 10.1021/jo400252n
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Multicomponent Synthesis of 2-Aryl-2-imidazolines from Aryl Halides and Diamines

Abstract: An efficient palladium-catalyzed three-component reaction that combines aryl halides, isocyanides, and diamines provides access to 2-aryl-2-imidazolines in yields up to 96%. Through variation of the diamine component, the reaction can be extended to the synthesis of 2-aryl-1H-benzimidazoles and 2-aryl-1,4,5,6-tetrahydropyrimidines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In 2013, Shipman and co-workers reported an efficient three-component reaction to synthesize 2aryl-2-imidazolines, in a palladium mediated catalytic cycle (70) (Scheme 20). [41] The reaction combines aryl halides (67), isocyanides (68), and diamines (69). Initially, different palladium catalysts and ligands were screened with ethylenediamine, tert-butyl isocyanide ( t BuNC), and phenyl iodide (PhI) and the authors identified two combinations of catalyst and ligand, as the most suitable for this reaction.…”
Section: Methods A: Synthesis Of Imidazolines From 12-diaminesmentioning
confidence: 99%
“…In 2013, Shipman and co-workers reported an efficient three-component reaction to synthesize 2aryl-2-imidazolines, in a palladium mediated catalytic cycle (70) (Scheme 20). [41] The reaction combines aryl halides (67), isocyanides (68), and diamines (69). Initially, different palladium catalysts and ligands were screened with ethylenediamine, tert-butyl isocyanide ( t BuNC), and phenyl iodide (PhI) and the authors identified two combinations of catalyst and ligand, as the most suitable for this reaction.…”
Section: Methods A: Synthesis Of Imidazolines From 12-diaminesmentioning
confidence: 99%
“…In 2014, Schipman et al extended the imidoylative Buchwald-Hartwig type cross-coupling to include the use of diamines 57 as coupling partners [43]. This reaction is indicative for imidoylative Buchwald-Hartwig couplings, and proceeds via the oxidative addition of an aryl halide 5 to in situ generated Pd 0 , after which a well-documented 1,1-migratory insertion of the isocyanide can take place.…”
Section: Cross-couplings With Oxygen or Nitrogen Nucleophilesmentioning
confidence: 99%
“…An efficient palladium‐catalyzed three‐component reaction that combined aryl halides, isocyanides, and 4‐substituted‐ ortho ‐phenylenediamine in the presence of toluene solvent provided access to 5‐substituted‐2‐phenyl‐benzimidazole 28 in 58% yield . The reflux was effected in PdCl 2 (5 mol%) and dppp (10 mol%) as shown in Scheme .…”
Section: Chemistrymentioning
confidence: 99%